The review of modern methods to evaluate users servicing quality - N. S. Redkina (Библиосфера, 2016)
Marketing methods of evaluating services of both readers and library users online are important to improve the quality of library-information servicing. The most commonly used methods to assess the quality of library services are statistical indicators analysis of activities (attendance, the number of resources/services access, etc.); surveillance; user survey; questionnaires; analysis of online services and Internet resources to determine the level of user satisfaction (online questionnaires, «like» estimates and others). In assessing satisfaction/dissatisfaction of users, their servicing quality such marketing tools as SERVQUAL, LibQUAL + TM, SERVPERF, «mystery shopper», «Kano methododology» and the concept of «neutral zones» by Ch. Bernard are more relevant. Their applying makes it possible to obtain accurate and complete information on the efficiency of employees’ work, to develop a program of activities and necessary recommendations to improve the quality of library servicing.